Registration for Work, Worksite Facilities and Management of Worksites under the Mahatma Gandhi NREGA in Kerala - S. Santhosh Kumar and M.Y. Helaney (Commerce Spectrum, 2015)
The paper examines the registration of beneficiaries for works, provision of worksite facilities and general worksite management under the Mahatma Gandhi NREGA in Kerala. The study found that the beneficiaries have positive perception regarding the registration for work, allotment of beneficiaries for work, worksite facilities provided and payment of wages under the Scheme. Region-wise differences in perception are also observed in the case of most of the constructs. Student's t-test and Kruskal Wallis ANOVA are used to compare the average responses of the construct variables across the regions.